ROAD SAFETY ASSESSMENT FOR ACCIDENT AND NON-ACCIDENT CASES SUPPORTING SUSTAINABLE DEVELOPMENT GOALS 2030 - Nugraha, Brian Nararya; Nurcahyati, Sekar Warangi; Adhikaratma, Hizkia; Siregar, Martha Leni (Journal of Environmental Science and Sustainable Development, 2024)
Halving the number of global deaths and injuries from road traffic accidents is one target of the Sustainable Development Goals 2030, which is still a challenging problem in Indonesia. However, the majority of research on this topic uses accident-based methods, which limits the safety analysis. Two road safety assessment methods are used to close the gap, with the addition of non-accident-based methods such as Road Safety Audits (RSA). The Margonda Raya Road, which is categorised as a traffic accident blackspot, was selected for the case study. For this, a field survey of the road segment is carried out. To minimise analysis bias, the RSA is conducted and finished first before the accident-based assessment. With the two combined methods, more safety concerns are successfully identified rather than using only one method. Several potential road safety risks were found through RSA, especially the hazard on the pedestrian crossings. For the accident-based method, a blackspot analysis and collision diagram are analysed based on 57 traffic accident data for over 3 years obtained from the Integrated Road Safety Management System (IRSMS). Accident-based data showed major findings of traffic accidents that happened at night with limited lighting. With countermeasures recommendation and implementation, the predicted crash is then calculated using the Crash Modification Factor (CMF). The countermeasures involve installing new solar-powered lighting to remove levelled pedestrian crossings, with a total cost of IDR 178,201,981. Based on the calculation, there is a potential to reduce 80% of the traffic accidents in this road segment. In addition, the calculation using the Benefit-per-Cost Ratio (BCR) showed a good result with a BCR value of 2.6. Improving the lighting is shown to have a potential impact on achieving the SDG targets in this sector and another sector that needs further research.